2022
DOI: 10.3389/fped.2022.1097836
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Exercise and childhood cancer

Abstract: Editorial on the Research Topic Exercise and childhood cancerGlobally, >175,000 children (i.e., individuals aged ≤18-21years) are diagnosed with cancer each year (1). For some of the most common cancers (e.g., acute lymphoblastic leukemia, non-Hodgkin lymphoma), medical advances have led to improved survival rates, with up to 85% expected to survive the disease for at least 5-years (1). 1 Despite improving prognoses, most children affected by cancer experience, or are at elevated risk, for numerous negative ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…However, none of the muscle ultrasound outcomes was associated with handgrip strength. This was somewhat surprising, because in healthy children hand grip strength is an indicator for general muscle strength 46 . This may not apply to children with ALL, because high-dose corticosteroids (as well as other chemotherapeutic agents) induce proximal muscle weakness rather than distal muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, none of the muscle ultrasound outcomes was associated with handgrip strength. This was somewhat surprising, because in healthy children hand grip strength is an indicator for general muscle strength 46 . This may not apply to children with ALL, because high-dose corticosteroids (as well as other chemotherapeutic agents) induce proximal muscle weakness rather than distal muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is usually known as age-related muscular deterioration, and is currently defined by the European Working Group on Sarcopenia in Older People as the presence of both low muscle mass and low muscle strength. 46 However, over the last decade it is shown that sarcopenia is a progressive and generalized skeletal muscle disorder associated with increased adverse health outcomes and mortality, not only in the elderly but in adults with various diseases as well. 46,47 Moreover, recent studies described this muscle disorder in chronically ill children and found associations between sarcopenia and postcolectomy complications in ulcerative colitis patients 48 , as well as increased perioperative length of stay, ventilator dependency, and readmissions in children after liver transplantation.…”
Section: Sarcopeniamentioning
confidence: 99%
See 3 more Smart Citations